Quantitative methods & their application in multidisciplinary area - Sharif, Shamshuritawati (Universiti Utara Malaysia Press, 2016)
This book is a guide for researchers who are involved in statistical and decision science analyses.Both analyses are explained in detail with samples of real applications in daily life to assist readers to appreciate theoretical and mathematical formulations. It covers a wide variety of applications, including economic issues, i.e., stock markets, quality control in the garment industry, customer satisfaction in the banking industry, experimental design in electronic firms, performance of university web portals, daily fat intake, the optimization of shrimp catching activities, meal planning for nurseries and as well as fairness model in economic games.Understanding these analyses can assist researchers to prepare research reports and manuscripts more efficiently.